PARADIGMA KARIR : PROTEAN CAREER MELALUI CONTINOUS LEARNING - Utama, Yudisthira Utama (Jurnal Analisis Bisnis Ekonomi, 2005)
The rapid changes of the business environment has causing the shifting organizaion structure and the career development of the individual. Career has shifting from the traditional careers into the modern careers. Protean career as the new paradigm of careers precisely answered the need of the modern careers in 21st century. Career will be driven by the individual not the organization, in which every individual needs to apply the continous learning in his or her careers. This paper describes the paradigm of career along with development in organization structure and provides the protean careers with continous learning as the career of 21st century.